Animal-based remedies as complementary medicines in Santa Cruz do Capibaribe, Brazil - Barboza Raynner RD; Souto Wedson MS; Tavares Marília C; Lima Helenice N; Alves Rômulo RN; Vasconcellos Alexandre (BMC, 2008)
Abstract Background The use of animal products in healing is an ancient and widespread cross-cultural practice. In northeastern Brazil, especially in the semi-arid region, animals and plants are widely used in traditional medicine and play significant roles in healing practices. Zootherapies form an integral part of these cultures, and information about animals is passed from generation to generation through oral folklore. Nevertheless, studies on medicinal animals are still scarce in northeastern Brazil, especially when compared to those focusing on medicinal plants. This paper examines the use and commercialization of animals for medicinal purposes in Brazil's semi-arid caatinga region. Methods Data was obtained through field surveys conducted in the public markets in the city of Santa Cruz do Capibaribe, Pernambuco State, Brazil. We interviewed 16 merchants (9 men and 7 women) who provided information regarding folk remedies based on animal products. Results A total of 37 animal species (29 families), distributed among 7 taxonomic categories were found to be used to treat 51 different ailments. The most frequently cited treatments focused on the respiratory system, and were mainly related to problems with asthma. Zootherapeutic products are prescribed as single drugs or are mixed with other ingredients. Mixtures may include several to many more valuable medicinal animals added to other larger doses of more common medicinal animals and plants. The uses of certain medicinal animals are associated with popular local beliefs known as 'simpatias'. We identified 2 medicinal species (Struthio camelus and Nasutitermes macrocephalus) not previously documented for Brazil. The use of animals as remedies in the area surveyed is associated with socio economic and cultural factors. Some of the medicinal animal species encountered in this study are included in lists of endangered species. Conclusion Our results demonstrate that a large variety of animals are used in traditional medicinal practices in Brazil's semi-arid northeastern region. In addition to the need for pharmacological investigations in order to confirm the efficiency of these folk medicines, the present study emphasizes the importance of establishing conservation priorities and sustainable production of the various medicinal animals used. The local fauna, folk culture, and monetary value of these activities are key factors influencing the use and commercialization of animal species for therapeutic purposes.